Jack Mason, the Old Sailor - Woodworth, Francis C. (Francis Channing); Woodworth, Francis Channing; Woodworth, F. C. (Francis Channing); Uncle Frank; Thinker, Theodore (Project Gutenberg, 2004)
The old sailor -- Jack Mason's visit to the North Sea -- The Indians -- The white bears -- Catching whales -- More Indians -- The little sailor boy -- The wreck -- The pyramids -- The whirlpool.